Management consultancy - Sturdy, Andrew (Oxford : Oxford University Press, 2009)
Management consultants are typically seen as key mediators in the flow of management ideas, yet little is known about what happens when they work together with clients, behind closed doors in consulting projects. Do they really innovate or simply legitimate existing knowledge? This book offers a 'fly on the wall' view.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Business consultants; Industrial sociology; Project management